Study on Dual-Stage Amplification Cascaded Piezoelectric Transducer for High-Power Applications - Li, Guo; Tan, Peiyu; Ma, Ruihui; Li, Feilong; Zhang, Xiaoli; Tian, Hua (Archives of Acoustics, 2026)
To reduce the size and enhance the efficiency of cascaded sandwich transducers with conical horns, a novel structural configuration of such transducers is investigated. This transducer incorporates two sets of piezoelectric stacks, enabling two-stage amplification to improve efficiency. An equivalent circuit model of the cascaded sandwich transducer with a conical horn is established, and analytical expressions for key performance parameters, including input impedance, velocity amplification ratio, and resonant characteristics, are systematically derived. Through theoretical and simulation analyses, the dynamic influence of key structural parameters on electromechanical energy conversion efficiency is determined, specifically including the output radius of the second stage, the relative position of the variable cross-sections of two sets of piezoelectric ceramic sandwich structures, and the spacing between the two sets of piezoelectric stacks. Furthermore, a performance optimization strategy based on piezoelectric single-crystal materials is proposed. Numerical simulation results, validated against the theoretical models, reveal the governing principles of piezoelectric material properties on transducer performance. Experimental results demonstrate excellent agreement between the operational characteristics of the optimized transducer and predictions obtained from both theoretical models and finite element simulations. This work provides significant guidance for the optimization of multi-mode transducers and demonstrates promising application potential in high-power ultrasonic fields.